Desempenho produtivo de vacas F1 Holandês/Zebu submetidas ao aumento de número de ordenha no início da lactação e a diferentes manejos de amamentação - Juliana Aparecida Mello Lima (2011)
The objective of this trial were to evaluate the effects of four daily milking until lactation day 21 and after this day two milking, with or without suckling by the calf, on milk yield and composition, daily weight gain of the calves, cows and calves weights and the reproductive parameters. Fifty three multiparous crossbred Holstein Zebu were distributed in four groups: 2BA - 12 cows were milked twice a day in the presence of their calves; 2BM - 13 cows were milked twice a day with theirs calves suckling in one teat during milking; 4BA - 15 cows were milked four times a day in presence of their calves and 4BM - 13 cows were milked four times a day with theirs calves suckling in one teat during milking. After day 21 all cows were milking twice a day. Milk production and composition were measured each four days until 33th day of lactation, and then each 15 days until the end of lactation. The animals were weighed at birth, 21 and 250 days of lactation. To analyze the financial viability of the different groups was used the gross margin, as financial indicator. The rise of milking frequency increased milk production in 2.04 kg/d, and in 17.3% of estimated gross margin from the sale of milk. The increase on milking frequency at the beginning of lactation did not influence the weight of cows and calves, service period or number of mount (P>0.05).